Neuroprotective Strategies – What Do We Really Need to Know? - Guzmán-Pruneda, Francisco A.; Fraser, Charles D. (Seminars in thoracic and cardiovascular surgery. Pediatric cardiac surgery annual, 2014)
While preliminary data are encouraging, definitive data are lacking to conclusively demonstrate the benefit of perioperative neurologic monitoring in improving neurodevelopmental outcomes in children who require surgery for congenital heart disease. Nonetheless, in the current era, some form of perioperative neurologic monitoring is important. Strategies include bicortical near infrared spectroscopy monitoring in the pre- and postoperative periods along with bicortical near infrared spectroscopy and transcranial Doppler intraoperatively. These monitors provide real-time information concerning cerebral oxygen delivery and blood flow. These strategies will allow us to refine treatments to optimize neurodevelopmental potential in children with congenital heart disease.